Synthesis and characterization of semicarbazide and thiosemicarbazide bearing butylated hydroxytoluene moiety for antioxidant application / Syabilah Sazeli - Syabilah , Sazeli (2021)
New multipotent antioxidants (MPAOs) semicarbazides and thiosemicarbazides bearing thiolated butylated hydroxytoluene (BHT) moiety were synthesized by a simple reaction between acid hydrazide, aryl isocyanates, and isothiocyanates. The antioxidant activity of these compounds was evaluated by using in vitro α, α-diphenyl-β-picrylhydrazyl (DPPH) assay. Thiosemicarbazides 5a’-h’ were found more active in free radical scavenging activity than semicarbazides 5a-h. Compound 2-(2-((3,5-di-tert-butyl-4-hydroxybenzyl)thio)acetyl)-N-(naphthalen-2-yl)hydrazine-1-carbothioamide 5f’ showed the best antioxidant activity against DPPH radical (IC50 of 25.47 ± 0.42 μM) compared to the standard BHT. Compound 5f’ and 2-(2-((3,5-di-tert-butyl-4-hydroxybenzyl)thio)acetyl)-N-(naphthalen-2-yl)hydrazine-1-carboxamide 5f were blended into trimethylolpropane trioleate (TMPTO) synthetic lube oil subjected for isothermal differential scanning calorimetric (DSC) measurement at 125 oC and 150 oC to investigate their oxidative stability. At 125 oC, TMPTO blended with 0.25 wt.% of 5f’ showed 2 and 1.5 times higher oxidative stability than that of BHT and 5f, respectively. It was postulated that the promising oxidative stability of 5f’ was due to strong auto-synergistic effect.